(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Any community or nation’s total economic progress depends on the social and economic advancement of its women. Every woman possesses the mindset of an entrepreneur, but it has not been given the recognition it deserves in India. People are now more at ease accepting leadership roles as a result of environmental changes. Women entrepreneurs are a subset of women who are pursuing new opportunities for economic engagement and have deviated from the norm. Women’s expertise, skills, and inventiveness in the business world, along with their strong desire to make a difference, are the main drivers behind their ownership of organized businesses. It is imperative that nations take up the challenge and establish additional support networks to promote women’s entrepreneurship. In India, women’s entrepreneurship has not grown much, particularly in rural areas. From the start of their business till it operates, female entrepreneurs deal with numerous challenges. In India, the role of women has been formally acknowledged since the Fifth Five Year Plan (1974–79), when the focus shifted from women’s welfare to women’s development and empowerment. Today, the importance of women in entrepreneurship is steadily growing as a result of numerous international factors. The Indian government has been putting a number of policies intoeffectincluding initiatives aimed at fostering women entrepreneurs in India. Indian women are praised for their accomplishments in their fields and stand out from the crowd in spite of all the social barriers.